Egy évszázados adósság – A Magyar Értelmiségi Adattár (Repertorium Academicum Hungariae) elkészítése - Szögi, László (Gerundium, 2017)
A centuries-old debt. The creation of the Hungarian Intellectuals’ Database (Repertorium Academicum Hungariae). Not school registers nor collections of archival sources were published about the Hungarian universities in the second half of the nineteenth and in the twentieth century. Similar books were publicised abroad much earlier about foreign institutions. Since Hungary has lost two third parts of its territory after the First World War the archival sources of these regions fell into foreign hands. Unfortunately,during the time of the Hungarian revolution in 1956 a few archival sources of the University Archives has also perished. Until nowadays we knew very little about students who were educated at universities or any other ecclesiastical or secular higher educational institutes. In 2013 the MTA-ELTE History of Universities Research Group was formed with the purpose of collecting and transforming into a database every available personal and educational information about every higher educational students from the beginning to 1850. The name of this future database will be Repertorium Academicum Hungariae. According to our current knowledge before 1850 there were 108 institutes in Hungary, Croatia and Transylvania which provided higher-level education than the intermediate level. We have already processed the two-thirds of the collected data and we are going to continue this task. The final database will be useable together with the completed database of the foreign-educated Hungarian students. The electronic database will be contain information about nearly 400,000 matriculated students and it will be unquestionably a useful scientific source for the nations of the Carpathian Basin.